Plant Disease Detection Methods using Image Processing - Gumber, Pankaj; Chand, Lal (International Journal of Computer Sciences and Engineering, 2019)
The image processing is the technique which can process the information stored in the form of pixels. The disease of the plants can be detected using the methods of image processing. The plant image has various types of noises which can affect accuracy of plant disease detection. In this work, various image de noising methods are reviewed and analyzed in terms of certain parameters.